New species of Poecilocloeus Bruner, 1910 (Orthoptera: Acrididae: Proctolabinae) from Paraná State, Brazil - Da Costa, Maria Kátia Matiotti; Fianco, Marcos; Martins, Fernando De Farias; Prasniewski, Victor Mateus; Szinwelski, Neucir; Zefa, Edison (Zootaxa, 2017)
In this study, we describe a new species of the genus Poecilocloeus from Renascença municipality, Paraná State, Brazil. Poecilocloeus renascensis n. sp. inhabits the Atlantic Semideciduous Forest edges of Renascença and adjacent areas, and our study is the first record of this genus from southern Brazil. The species belongs to the group bullatus (Rehn, 1908), and the descriptions are based on morphological characters, mainly from male genitalia. Morphological descriptions are provided together with illustrations emphasizing the most significant diagnostic features of external morphology and male genitalia. Information is given about type specimens, examined material and geographic distribution.